Differences in Teenagers' Attitudes About Early Marriage Before and After Providing Education Through Leaflet at Asy Syuja’i High School in Jember - Kartika Sari, Vieky; Aby Restanty, Dian; Kiswati, Kiswati (Universitas Bondowoso, 2025)
Introduction: Background: In 2022, 33.77% of Indonesian teenagers reported marrying for the first time when they were between 19 and 21 years old. This statistic comes from the Central Bureau of Statistics (BPS). In addition, 19.24% of teenagers married for the first time between the ages of 16 and 18. The province with the highest rate of child marriage in 2022-10.44% higher than the national average-is East Java Province. Teenagers' attitudes towards early marriage are one of the factors that influence the prevalence of early marriage. Teenagers' views and personalities are reflected in their attitudes. The aim of this study was to compare teenagers' opinions on early marriage before and after they received instructions through leaflets. Method: A one-group pretest and posttest was used in the design of this study. Saturated sampling was used in the sampling process. There were sixty respondents in the sample. The paired t-test was the statistical analysis method used in this investigation Result: Teenagers who received education had 13.3% fewer attitudes before and 0% fewer after receiving education. Paired T-test analysis yielded a p value of 0.000 < α 0.05, indicating a change in teenagers' opinions about early marriage between before and after they received education through leaflets. In summary, there was a difference in the mean scores on the pretest and posttest: the former was 35.08 and the latter rose to 39.33 after schooling. Conclusion: The use of leaflets allows schools to provide education and learning materials on early marriage to teenagers.